Problematika Perizinan Penyiaran Berbasis Digital Antara Undang-Undang Penyiaran Dan Undang-Undang Cipta Kerja Di Indonesia - Rifqi, Haykal (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
Disharmonization and legal vacuum in digital broadcasting licensing, by looking at the Broadcasting Law and the Job Creation Law which have different paradigms for granting permits for entities that want to carry out broadcasting, such as YouTube, Netflix, etc. The lack of harmony with existing regulations, as well as the vacuum in the digital broadcast licensing law in the Broadcasting Law, of course has the effect of different treatment between conventional and digital. This research uses a normative juridical approach accompanied by literature study in the form of books, journals and other literature. The author also uses comparative models and descriptive analysis in managing qualitative data accompanied by deductive methods. The research results show that the provisions of the Broadcasting Law relate to how to regulate broadcast formats as a license, but only for conventional broadcasting. The Job Creation Law is actually oriented towards facilitating licensing by equalizing the position of broadcasting institutions with legal entities in other sectors without paying attention to the content of their broadcast’s, even digital broadcasting licensing has not yet been regulated regarding the ideal form of supervision. The Job Creation Law is too directed at capitalism so there is a need for legal reform, by looking at the models of other countries such as Turkey